MANAJEMEN KONFLIK DALAM MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR KECAMATAN ALAS BARAT KABUPATEN SUMBAWA - Syafruddin, S; Arafah, Muhammad (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to determine the effect of conflict management on employee work productivity in Alas Barat Sub-District, Sumbawa District. The type of this study was associative study used to examine the significance effect of conflict management on employee work productivity in Alas Barat Sub-District, Sumbawa District. The type of data used in this study was quantitative data obtained directly through questionnaires distributed to respondents, namely all employees at the Alas Barat Sub-District Office, Sumbawa District. The number of respondents in this study was 18 people who were determined using a saturated sampling technique (census sampling). In this research, the data was processed using the SPSS computing program, to be analyzed using simple linear regression analysis techniques, partial hypothesis testing (t test), and coefficient of determination test (R2). The results of this study showed that conflict management had a positive and significant effect on employee work productivity at the Alas Barat Sub-District Office, Sumbawa District. The contribution effect of conflict management on employee work productivity at the Alas Barat Sub-District Office, Sumbawa District was 54.3%, while the remaining of 45.7% was effected by other factors outside this study model, such as suitability of wages, education level, work and managerial experience.